5-Aminolevulinic Acid False-Positive Rates in Newly Diagnosed and Recurrent Glioblastoma: Do Pseudoprogression and Radionecrosis Play a Role? A Meta-Analysis - Ricciardi, Luca; Sturiale, Carmelo Lucio; Scerrati, Alba; Stifano, Vito; Somma, Teresa; Ius, Tamara; Trungu, Sokol; Acqui, Michele; Raco, Antonino; Miscusi, Massimo; Della Pepa, Giuseppe Maria (Frontiers in Oncology, 2022)
Background Several studies have confirmed the impact of 5-aminolevulinic acid (5-ALA) on the extent of resection in newly diagnosed glioblastoma (GBM). However, there are controversies on the 5-ALA fluorescence status in recurrent GBM surgery, with specific reference to pseudoprogression or radionecrosis; therefore, the safety and accuracy of surgical planning in 5-ALA-assisted procedures in the recurrent context are still unclear. Materials and Methods This is a systematic review and meta-analysis of comparative studies on the use of 5-ALA in newly diagnosed and recurrent GBM, consistently conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement. Data on fluorescence status and correlation between fluorescence and histological findings were collected. We performed a meta-analysis of proportions to estimate the pooled rates of each outcome. Results Three online medical databases (PubMed, Scopus, Cochrane Library) were screened, 448 articles were evaluated, and 3 papers were finally included for data analysis. Fluorescence rate was not different between newly diagnosed and recurrent GBM [p = 0.45; odds ratio (OR): 1.23; 95% CI: 0.72–2.09; I2 = 0%], while the rate of 5-ALA fluorescence-positive areas not associated with histological findings of GBM cells was higher in recurrent GBM (p = 0.04; OR: 0.24; 95% CI: 0.06–0.91; I2 = 19%). Furthermore, there were no cases of radionecrosis in false-positive samples, while inflammation and signs of pseudoprogression were found in 81.4% of the cases. Discussion and Conclusions Therefore, a robust awareness of 5-ALA potentialities and pitfalls in recurrent GBM surgery should be considered for a cognizant surgical strategy. Further clinical trials could confirm the results of the present meta-analysis.